2019
DOI: 10.1088/1755-1315/277/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Screening of polyhydroxyalkanoates (PHA)-producing bacteria from soil bacteria strains

Abstract: Plastic wastes and petrochemical-based polymer materials have become a serious problem to the environment due to the characteristics of these materials that are difficult to degrade in nature. Polyhydroxyalkanoates (PHA) is one type of biodegradable plastics that have a great potential to replace the widely-used hydrocarbon plastics since it will decompose completely into carbon dioxide and water after burial for several months in the soil. PHA can be produced by microorganisms such as bacteria and algae throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Tan et al [2014a] demonstrated that, Nile blue staining provides an evidence for the production of PHAs which enabled microbe producers to be isolated and identified. Ratnaningrum et al [2019] stated that all the studied colonies confirmed to be able to present the cells that fluoresce under a fluorescent microscope.…”
Section: Results and Discussion Isolation And Screening Of The Pha Producing Bacteriamentioning
confidence: 83%
“…Tan et al [2014a] demonstrated that, Nile blue staining provides an evidence for the production of PHAs which enabled microbe producers to be isolated and identified. Ratnaningrum et al [2019] stated that all the studied colonies confirmed to be able to present the cells that fluoresce under a fluorescent microscope.…”
Section: Results and Discussion Isolation And Screening Of The Pha Producing Bacteriamentioning
confidence: 83%
“…It is important to note that the production of PHB by Burkholderia sp. B73 was 52.9% in Ramsay's minimal medium (Ratnaningrum et al, 2019). In this study, we reveal that the yield of PHB obtained by using molasses as substrate was two times higher.…”
Section: Effect Of Initial Ph Value On Phb Yieldmentioning
confidence: 56%
“…1B). The data have been accomplished in the previous research (Ratnaningrum et al, 2019). Therefore, Burkholderia sp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations